Navigating Complex Endodontic Challenges: A Comprehensive Review of Guided Treatment Strategies - Shanmugasundaram, Srilaatha; Pandit, Varsha; Hegde, Vivek; Pathan, Sumayya; Doshi, Saurabh; Mujawar, Asiya (Journal of Neonatal Surgery, 2025)
The field of endodontics has undergone a significant transformation with the advent of guided techniques aimed at enhancing precision and predictability in managing complex cases. Conventional methods often fall short in scenarios involving calcified canals, developmental anomalies, or retreatments. This review explores the evolution and application of guided endodontic techniques, including static navigation, dynamic navigation, and guided microsurgical strategies. Through a synthesis of available literature and clinical cases, we highlight the indications, advantages, and current limitations of these approaches. Additionally, the article discusses future trends, including AI integration and advanced 3D printing, which may broaden the clinical accessibility and efficacy of guided endodontics. The review concludes by emphasizing the need for meticulous planning and proper case selection to maximize outcomes in complex endodontic scenarios